Communication, multiplying the message - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
The need to inform, educate and motivate rural people in ACP countries has never been greater because there are more mouths to be fed but fewer, and older, hands to produce the food. Many farmers still lack the basic knowledge and self confidence to...